2022
DOI: 10.3390/antibiotics11091145
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Consumption Patterns in European Countries Are Associated with the Prevalence of Parkinson’s Disease; the Possible Augmenting Role of the Narrow-Spectrum Penicillin

Abstract: Parkinson’s disease: Parkinson’s disease (PD) is the second-most common neurodegenerative disease, affecting at least 0.3% of the worldwide population and over 3% of those over 80 years old. According to recent research (2018), in 2016, 6.1 million (95% uncertainty interval (UI) 5.0–7.3) individuals had Parkinson’s disease globally, compared with 2.5 million (2.0–3.0) in 1990. The pandemic-like spreading of PD is considered a slow-moving disaster. Most recent studies indicated the possible role of an altered m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…This question may have been partially answered in this study because Neu-REFIX beta-glucan has shown beneficial effects of restoring the gut microbiome and also the improvement in clinical parameters could be attributed as an effect. Going by the earlier reports of gut dysbiosis caused by specific drugs in neurological illness [17,18], in line with those evidences, whether similar drugs are part of MS regimen have to be looked into or diseases that have direct correlation to gut dysbiosis when subjected to a clinical study, the appropriate drug or molecule should be studied for implications on gut microbiome as well.…”
Section: Discussionmentioning
confidence: 94%
“…This question may have been partially answered in this study because Neu-REFIX beta-glucan has shown beneficial effects of restoring the gut microbiome and also the improvement in clinical parameters could be attributed as an effect. Going by the earlier reports of gut dysbiosis caused by specific drugs in neurological illness [17,18], in line with those evidences, whether similar drugs are part of MS regimen have to be looked into or diseases that have direct correlation to gut dysbiosis when subjected to a clinical study, the appropriate drug or molecule should be studied for implications on gut microbiome as well.…”
Section: Discussionmentioning
confidence: 94%
“…The analysis of the collateral effect of antibiotics on the gut microbiome indicated that tetracycline/doxycycline reduced the abundance of several commercial components of the microbiome isolates, most effectively, E. coli , even at low concentrations [ 50 ]. Interestingly enough, the use of narrow-spectrum penicillin and tetracycline might also be associated with the prevalence/incidence of certain neurodegenerative diseases, such as PD and MS [ 51 , 52 , 53 ]. Maternal microbial dysbiosis has been implicated in adverse postnatal health conditions in offspring, such as obesity, cancer, and neurological disorders, but in the case of DS, most of the available literature is focused on maternal risk factors, and the only certain risk factors for the birth of a child with DS are advanced maternal age at conception and recombination errors, even though the molecular mechanisms leading to chromosome 21 nondisjunction are still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the collateral effect of antibiotics on the gut microbiome indicated that tetracycline/doxycycline reduced the abundance of several commercial components of the microbiome isolates, most effectively E. coli, even at low concentrations [50]. Interestingly enough that the use of narrow-spectrum penicillin and tetracycline might be associated with the prevalence/incidence of certain neurodegenerative diseases also, like PD and MS [51][52][53]. Maternal microbial dysbiosis has been implicated in adverse postnatal health conditions in offspring, such as obesity, cancer, and neurological disorders, but in the case of DS, most of the publications are focused on maternal risk factors, and the only certain risk factors for the birth of a child with DS are advanced maternal age at conception and recombination errors, even though the molecular mechanisms leading to chromosome 21 nondisjunction are still uncertain.…”
Section: Discussionmentioning
confidence: 99%